Age and immunity: What is “immunosenescence”? - Pawelec, Graham (Experimental gerontology, 2018)
As is apparent from the many contributions to this Special Issue of the Journal, the impact of age on immunity is nefarious, with all manner of dysregulated responses attributed to “immunosenescence”. These range from poorer responses to vaccination, lower capacity to mediate anti-cancer responses, more inflammation and tissue damage, along with autoimmunity and loss of control of persistent infections. Given the grave clinical implications of altered immune status in aged people, it is of paramount importance to understand the nature of and mechanisms responsible for “immunosenescence”. As in any rapidly developing research area, certain paradigms establish themselves early on, by necessity based on earlier and fewer data, and have a disproportionate influence on how investigators think about the subject, especially investigators from other disciplines. It may therefore be appropriate to reconsider our basic knowledge at this juncture, asking exactly what do we mean by the term “immunosenescence”? This is attempted in this contribution to the Special Issue. •Opinion on the nature of immunosenescence•Opinion on inflammageing•Importance of longitudinal studies in humans